Effect of Boiled Carica Papaya Leaf on Death of Aedes Aegypti Larvae - Rustam Aji (Masters Program in Public Health, 2017)
Background: In its life cycle Aedes aegypti larvae develop to become mosquito. Then the masquito develops to become vector of dengue haemorrhagic fever transmission. The life cycle of Aedes aegypti vector can be interrupted by killing Aedes aegypti larvae. The killing of Aedes aegypti larvae has been undertaken by fogging or abate powder administration. However, these methods can cause environmental pollution. Carica papaya leaf has long been recognized to have the potential to become an effective and safe larvacide since it contains papain enzyme. The effect of papain protease can kill Aedes aegypti larvae. This study aimed to determine the effect of boiled Carica papaya leaf on death of Aedes aegypti larvae.Subjects and Method: This was an analytic experimental study using randomized control trial design. The study was conducted in Curup Tengah village, Bengkulu Province. Study sample included 36 water containers containing Aedes aegypti larvae. These containers were divided into 2 groups: papain enzyme group and no papain enzyme (control) group. The data on the percentage of killed Aedes aegypti larvae were then compared and tested by Chi Square test. The effect of Carica papaya leaf was indicated by Odds Ratio.Results: Boiled Carica papaya leaf had an effect on the death of Aedes aegypti larvae. Carica papaya leaf that was administered on the larvae increased the risk of death among Aedes aegypti larvae four times as many (OR= 4.10; p= 0.043). Conslusion: Carica papaya leaf is effective to increase the risk of death among Aedes aegypti larvae.Keyword : Carica papaya leaf, Aedes aegypti larvae.Correspondence: Rustam Aji. Study Program in Nursing, Curup School of Health Polytechnics, Bengkulu. Email: adjieroestamadjie@gmail.com.Journal of Epidemiology and Public Health (2017), 2(3): 236-240https://doi.org/10.26911/jepublichealth.2017.02.03.05